Glomus Tumor of the Stomach: A Rare Cause of Upper Gastrointestinal Bleeding. (29th October 2011) - Nascimento, Enzo Fabrício Ribeiro; Fonte, Fábio Piovezan; Mendonça, Roberta Laís; Nonose, Ronaldo; de Souza, Carlos Alberto Fonte; Martinez, Carlos Augusto Real
Abstract : Introduction . Glomus tumors (GTs) are benign neoplasm originating from the glomus body, commonly described in subungual region. The involvement abdominal is rare. Our aim is to describe a case of glomus tumor of the stomach that presented upper gastrointestinal bleeding. A 34-year-old woman was admitted with upper gastrointestinal bleeding and underwent an upper endoscopy that showed bleeding arising from an ulcerated lesion, treated by sclerosis therapy. A new endoscopy confirmed a submucosal lesion in upper portion of the stomach. During the laparotomy, a tumor at the upper anterior wall of gastric body was found and resected by a vertical gastrectomy. The pathological exam revealed hyperplastic smooth muscle fibers of the muscularis propria of the stomach wall, surrounded by hyaline stroma. The immunohistochemistry panel was positive for smooth muscle actin and type IV collagen, with low rate of mitosis studied by Ki-67 which allowed the final diagnosis of a gastric glomus tumor. Discussion . The majority of intraperitoneal glomus tumors occur in the stomach, and it is phenotypically similar to those localized in peripheral sites. Gastric GT generally is a benign tumor although it can be malignant and have the potential to metastasize. Conclusion . Even though gastric glomus tumor is rarely described, it should be considered as a possible cause of a major upper gastrointestinal bleeding.